Vaideśikanītau Ṣāḍguṇya-siddhāntaḥ - Jhā, Jīvānanda (Jānakī Prakāśana, 2017)
Foreign policy in relation to Sanskrit literature
Literaturverzeichnis: Seite 165-171
Keywords: Altindisch; Literatur; Politik; Internationale Politik; Dharmashastra; Nītiśāstra